Vocational Process of College Students in Statuses of Achievement and Academic Lagging: An Analysis from the Donald Super's Evolutionary Approach - Raquel María Bulgarelli-Bolaños; José Antonio Rivera-Rodríguez; Manuel Arturo Fallas-Vargas (Universidad Nacional, Costa Rica, 2016)
This article is based on an investigation whose main purpose was to analyze students' vocational development in statuses of achievement and academic lagging in Bachelor's Degree in Industrial Chemistry at the Universidad Nacional de Costa Rica, during 2014, by implementing Donald Super's evolutionary approach. A naturalist paradigm, a design of collective case studies of four people (two students from each academic status), four data gathering tools (in-depth interviews, semi-structured interviews, in-depth discussion meetings, and observation), and the categorical thematic analysis method were applied. It was found that there are differences in the vocational process of the four cases studied when referring to one academic status or the other, where the category of achievement is more leaning trend to a better vocational performance, even though it is not a predictor of this; while the academic lagging presents more difficulties in its different vocational stages. Therefore, it is recommended not to neglect academic, vocational and personal-social support to any of both populations, considering their particularities related to the specific vocational processes and the evaluations they carry out during the career.